Treatment of food waste recycling wastewater using anaerobic ceramic membrane bioreactor for biogas production in mainstream treatment process of domestic wastewater. (15th October 2017) - Jeong, Yeongmi; Hermanowicz, Slawomir W.; Park, Chanhyuk
Abstract: A bench-scale anaerobic membrane bioreactor (AnMBR) equipped with submerged flat-sheet ceramic membranes was operated at mesophilic conditions (30–35 °C) treating domestic wastewater (DWW) supplemented with food wasterecycling wastewater (FRW) to increase the organic loading rate (OLR) for better biogas production. Coupling ceramic membrane filtration with AnMBR treatment provides an alternative strategy for high organic wastewater treatment at short hydraulic retention times (HRTs) with the potential benefits of membrane fouling because they have a high hydrophilicity and more robust at extreme conditions. The anaerobic ceramic MBR (AnCMBR) treating mixture of actual FRW with DWW (with an influent chemical oxygen demand (COD) of 2, 115 mg/L) was studied to evaluate the treatment performance in terms of organic matter removal and methane production. COD removal during actual FRW with DWW operation averaged 98.3 ± 1.0% corresponding to an average methane production of 0.21 ± 0.1 L CH4 /g CODremoved . Biogas sparging, relaxation and permeate back-flushing were concurrently employed to manage membrane fouling. A flux greater than 9.2 L m −2  h −1 (LMH) was maintained at 13 h HRT for approximately 200 days without chemical cleaning at an OLR of 2.95 kg COD m −3  d −1 . On day 100, polyvinyl alcohol (PVA)-gel beads were added into the AnCMBR to alleviate the membrane fouling, suggesting that their mechanical scouring effect contributed positively in reducing the fouling index (FI). Although these bio-carriers might accelerate the breaking up of bio-flocs, which released a higher amount of soluble microbial products (SMP), a 95.4% SMP rejection was achieved. Although the retention efficiency of dissolved organic carbons (DOC) was 91.4% across the ceramic membrane, a meaningful interpretation of organic carbon detection (OCD) fingerprints was conducted to better understand the ceramic membrane performance. Graphical abstract: Image 1 Highlights: A new approach was introduced for energy recovery in mainstream treatment of domestic wastewater. AnCMBR treatment was successfully applied for treating food waste recycling wastewater. The positive effect of PVA-gel beads addition was observed in the AnCMBR. Dissolved organic matters (DOMs) removal by ceramic membranes was studied.